2019
DOI: 10.3390/ijerph16122184
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Exercise on Physical Function, Cognition and Hemodynamic Parameters of Community-Dwelling Older Adults: A Quasi-Experimental Study

Abstract: This paper reports on a quasi-experimental study that aimed to identify changes in muscle function (i.e., mobility, maximal walking speed, lower limb muscle strength, balance, and transfer capacity), cognition (i.e., executive function) and hemodynamic parameters of community-dwelling Brazilian older adults during a six-month multicomponent exercise program (MCEP). A total of 436 community-dwelling older adults performed functional, cognitive and hemodynamic assessments before and after a six-month MCEP. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
(87 reference statements)
3
11
0
2
Order By: Relevance
“…The results also demonstrated a meaningfully higher static and dynamic balance of the experimental group than the control group. Similar results were found by Wongcharoen et al [ 35 ], where balance rapidly increased after a 12-week seniorobics program, and by Oliveira Goncalves et al [ 36 ], where 16-week exercise programs customized for fall prevention were shown to be effective. Static balance is the basic ability to maintain a stable center of the body and is a requirement for a safe everyday life [ 36 ].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The results also demonstrated a meaningfully higher static and dynamic balance of the experimental group than the control group. Similar results were found by Wongcharoen et al [ 35 ], where balance rapidly increased after a 12-week seniorobics program, and by Oliveira Goncalves et al [ 36 ], where 16-week exercise programs customized for fall prevention were shown to be effective. Static balance is the basic ability to maintain a stable center of the body and is a requirement for a safe everyday life [ 36 ].…”
Section: Resultssupporting
confidence: 85%
“…Moreover, loneliness (t = −3.02, p = 0.003) and role self-efficacy (t = 2.39, p = 0.020) improved statistically significantly compared to the control group. The results of this study supported the previous studies [2,14,18,35,36,38,39]. However, ego integration score improved after the program, but there was no significant difference between the experimental and control groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the relationship between this type of exercise and cognitive functions is unclear, the effectiveness of physical exercise in reducing frailty and improving cognition, emotions, and social networks has been reported among frail older adults [ 16 ], using multicomponent exercise and including aerobic exercise. This fact makes difficult to isolate the effect of the multicomponent exercise intervention approach, whose evidence on cognition remains inconclusive [ 36 ], as well as the most suitable combination of components, duration and dose [ 37 ]. Nevertheless and considering that physical activity is part of the intervention of the vast majority of conditions that affect older people, the inclusion of an individualized physical exercise in the management of the older patients should be part of the daily clinical practice [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Latin American countries, public health and PE institutions guide the community regarding PE realization to improve endurance, strength, balance, flexibility and quality of life in OA (ACEMI, 2011; Dirección de Promoción de la Salud y Control de Enfermedades No Transmisibles, 2013; Gobierno de Chile, 2017; Ministerio de Salud Pública del Ecuador, 2011; Secretaria Nacional de Deporte, 2018), proposing as alternative activities the ones in the aquatic environment (Secretaria Nacional de Deporte, 2018). Several studies have also been conducting programs using multi-component PE, where aerobic capacity, flexibility, balance, strength, and cognitive performances were increased, decreasing on the other hand symptoms of depression or anxiety (Bueno et al, 2018;Carvalho et al, 2009;Gonçalves et al, 2019;Nacional Costa Rica et al, 2018;Rico-Gallegos et al, 2020;Salinas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%